Cyber Victimization Is Associated With Eating Disorder Psychopathology in Adolescents - Marco, Jose H.; Tormo-Irun, M. Pilar (Frontiers in Psychology, 2018)
Technology is constantly evolving in a vast number of fields. In this way, cyber victimization is associated with psychopathology, and body appearance is a primary target of cyberbullies. Thus, the literature demonstrates a clear association between bullying and unhealthy eating behaviors in adolescents. However, studies that have examined the association between Cyber victimization and eating disorder psychopathology are scarce. Objective: 1) To analyze whether there are differences in the cyber victimization scores depending on the gender, controlling for age; (2) to analyze whether cyber victimization is negatively associated with eating disorder psychopathology; (3) to analyze whether this association is moderated by the level of Appearance Evaluation. Method: Participants in the present study included 676 adolescents, 367 girls and 309 boys from several cities of Spain. The mean age for the overall sample was 14.28 years (SD = 1.65), ranging from 12 to 19. The participants filled out the questionnaires ECIPQ, MBSRQ, and EAT. Results: Cyber victimization was associated with eating disorders psychopathology, Appearance Evaluation, and Overweight Preoccupation. Appearance Evaluation moderated the association between Cyber victimization and the eating disorder psychopathology. Conclusion: It is necessary to assess vulnerability to eating disorders in adolescents who have been victims of cyberbullying.